THE CONCEPT OF DIGITAL TRANSFORMATION AND ITS IMPACT ON INDUSTRIAL SYSTEMS - Tyurahanov Shamsitdin Djamshid o‘g‘li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article provides an in-depth analysis of the theoretical foundations of the concept of digital transformation and their impact on traditional industrial systems. Digital technologies - IoT, artificial intelligence, Big Data and cloud systems - are becoming an important factor in increasing the efficiency of industrial enterprises, improving the level of resource utilization and accelerating the process of strategic decision-making. Based on international experience, the advantages and limitations of digital transformation are identified, the state of readiness of the Uzbek industry for digital development is assessed, and scientific proposals are developed for the transition to a digital model of management.